2010
DOI: 10.1038/ja.2010.128
|View full text |Cite
|
Sign up to set email alerts
|

Genome mining and biosynthesis of fumitremorgin-type alkaloids in ascomycetes

Abstract: This review summarizes the recent progress on the biosynthesis of fumitremorgin-type alkaloids; that is, the identification of the biosynthetic gene clusters from genome sequences by genome mining and proof of gene function by molecular biological and biochemical investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…In the biosynthesis of stephacidin, notoamides and brevianamides, cyclo-L-Trp-L-Pro (brevianamide F, 9a) is reverse prenylated at the C-2 position of the indole ring (Ding et al, 2010;Li, 2011). A gene cluster for the biosynthesis of these compounds and two brevianamide F prenyltransferases (NotF and BrePT) has been reported recently (Ding et al, 2010;Yin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the biosynthesis of stephacidin, notoamides and brevianamides, cyclo-L-Trp-L-Pro (brevianamide F, 9a) is reverse prenylated at the C-2 position of the indole ring (Ding et al, 2010;Li, 2011). A gene cluster for the biosynthesis of these compounds and two brevianamide F prenyltransferases (NotF and BrePT) has been reported recently (Ding et al, 2010;Yin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…stephacidin, notoamides and brevianamides derived from L-tryptophan and L-proline, echinulins from L-tryptophan and L-alanine, as well as fellutanines from two tryptophan molecules (Ding et al, 2010;Li, 2010Li, , 2011Wang et al, 2007;Williams et al, 2000). A C2-prenylated (S)-benzodiazepinedione (1b) or derivatives have not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…The first identified cyclic dipeptide prenyltransferase was FtmPT1 from A. fumigatus, which catalyzes a regular C2-prenylation of brevianamide F (cyclo-L-Trp-L-Pro) in the biosynthesis of verruculogen/fumitremorgins (Grundmann and Li 2005;Li 2011). Three cyclic dipeptide reverse C2-prenyltransferases, NotF from an Aspergillus sp.…”
Section: Tryptophan-containing Cyclic Dipeptide and Related Prenyltramentioning
confidence: 99%
“…9,10) The putative FTM biosynthetic gene cluster was found by genome sequencing of the human pathogen A. fumigatus. 11,12) A genetic study of a nonribosomal peptide synthetase gene, ftmA, and biochemical studies of two prenyltransferase genes, ftmB and ftmH (also termed ftmPT1 and ftmPT2, respectively), showed that the ftm cluster is associated with the FTM biosynthetic pathway, 4,13,14) but no FTM production was detected in a genome reference strain of A. fumigatus, Af293. 13) Hence, we utilized an FTMproducing strain of A. fumigatus, BM939, 15) to dissect the FTM pathway, and demonstrated the functions of three cytochrome P450s, FtmC, FtmE, and FtmG, in the biosynthetic pathway.…”
mentioning
confidence: 99%